Switching costs in the European postal service. Are there any solutions? - Carlos Pateiro-Rodriguez; Javier Prado-Domińguez; Jesuś Manuel Garciá-Iglesias; JoseḾanuel Barreiro-Vin\~ań (European Journal of Government and Economics (EJGE), 2017)
This article examines the costs of switching that may exist in the European postal sector, where it is carried out an ambitious process of opening to competition since 1997. Inadequate regulation of the access to some elements of postal infrastructure or services within the scope of the universal postal service exists. This article proposes adaptations to ensure transparent and non-discriminatory access conditions to elements of postal infrastructure in line with the sectorial directives aimed at strengthening competition in the long term in the postal market. The proposed adaptations focus on services such as postcode systems, address databases, post office boxes, delivery boxes, re-direction and return to sender services. All of them can help reduce the switching cost and thus strengthen competition.
Keywords: 330; Liberalization; Universal postal service; Switching costs; Postal network